Handbook of industrial cell culture: Mammalian, microbial, and plant cells - Vinci, Victor A (Humana Press, 2012)
Describes in simple language, the major technologies for improving the biocatalytic capabilities of mammalian, microbial, and plant cells. The authors present state-of-the-art techniques, proven methods, and strategies for industrial screening, cultivation, and scale-up of these cells, and describe their biotech and industrial uses.